Collective behaviour in high and low-level youth soccer teams. Issue 2 (3rd April 2022) - O'Brien-Smith, Jade; Fransen, Job; Sheehan, William B.; Lenoir, Matthieu; Bennett, Kyle; Smith, Mitchell R.
ABSTRACT: Background: An expert/non-expert paradigm often helps understand the underpinnings of sports expertise; however, this method is scarcely extended to the complexities of collective behaviour in youth soccer. Aim: Therefore, the objectives of the current study are to investigate differences in the collective behaviour of youth soccer teams by expertise level. Methodology: Soccer players aged 15 to 20 years from high (n = 35) and low (n = 40) playing levels competed in two age-matched 5v5 small-sided games. For each game, teams' skill involvement (shot, pass, dribble, touch), passing networks (closeness, density, betweenness), and spatiotemporal characteristics (stretch index, effective area, length (L) & width (W), LpW ratio, synchrony) were measured using video footage and GPS coordinates. Results: High level teams had more attempted (p = .009), and completed skills (p = .003), particularly for the number of passes (p = .001) and shots (p = .012-.045). However, there were no significant between-group differences for either the passing networks or spatiotemporal characteristics. Conclusion: The findings from the current research suggest that the high-level teams can quickly and effectively move the ball within existing team structures and may better optimise their afforded space to execute desired skills when compared to the low-level teams.